PERAN MAHASISWA PPL DALAM INOVASI PEMBELAJARAN DI SMA SUNAN DRAJAT SUGIO - Fatimatus Sa'diyah; Irfa’ Uddarojah; Ifana Dwi Ratna Suri; Sutardi Sutardi; Badi’ Zamani Rohman (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
Learning innovation is a crucial element in improving the quality of education at the secondary school level, particularly in the context of the implementation of the Merdeka Curriculum, which emphasizes student-centered, contextual, and adaptive learning. However, classroom practices in many schools still face challenges, such as the dominance of conventional teaching methods and limited variation in learning media. In this context, pre-service teachers participating in the Teaching Practicum Program (Program Pengenalan Lapangan/PPL) have the potential to act as agents of change by bringing fresh ideas, technological skills, and innovative instructional approaches. This study aims to describe the role of PPL students in promoting learning innovation at SMA Sunan Drajat Sugio and to identify the forms of learning innovation implemented during the practicum period. This research employed a qualitative descriptive approach with a case study design. The research subjects included PPL students, mentor teachers, and students of SMA Sunan Drajat Sugio. Data were collected through classroom observations, in-depth interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing techniques. The findings reveal that PPL students played a significant role as initiators of learning innovation through the use of digital media, the application of active learning models, and the integration of technology in classroom instruction. These innovations received positive responses from both teachers and students and contributed to increased student engagement and learning motivation. The study concludes that PPL students have a strategic role in fostering learning innovation and can serve as valuable partners for schools in developing more innovative learning practices. ABSTRAK Inovasi pembelajaran merupakan aspek penting dalam peningkatan kualitas pendidikan di sekolah menengah, terutama pada era implementasi Kurikulum Merdeka yang menekankan pembelajaran berpusat pada peserta didik, kontekstual, dan adaptif terhadap perkembangan zaman. Namun, dalam praktiknya, pembelajaran di sekolah masih menghadapi berbagai tantangan, seperti dominasi metode konvensional dan terbatasnya variasi media pembelajaran. Dalam konteks ini, mahasiswa Program Pengenalan Lapangan (PPL) memiliki potensi sebagai agen perubahan pembelajaran karena membawa gagasan baru, penguasaan teknologi, serta pemahaman terhadap pendekatan pembelajaran inovatif. Penelitian ini bertujuan untuk mendeskripsikan peran mahasiswa PPL dalam inovasi pembelajaran di SMA Sunan Drajat Sugio serta mengidentifikasi bentuk-bentuk inovasi pembelajaran yang diterapkan selama pelaksanaan PPL. Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan desain studi kasus. Subjek penelitian meliputi mahasiswa PPL, guru pamong, dan siswa SMA Sunan Drajat Sugio. Data dikumpulkan melalui observasi pembelajaran, wawancara mendalam, dan dokumentasi, kemudian dianalisis menggunakan teknik reduksi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa mahasiswa PPL berperan sebagai inisiator inovasi pembelajaran melalui penggunaan media digital, penerapan model pembelajaran aktif, serta integrasi teknologi dalam pembelajaran. Inovasi tersebut mendapat respons positif dari guru dan siswa serta berdampak pada meningkatnya keterlibatan dan motivasi belajar siswa. Penelitian ini menyimpulkan bahwa mahasiswa PPL memiliki peran strategis dalam mendorong inovasi pembelajaran dan dapat menjadi mitra penting sekolah dalam pengembangan pembelajaran yang lebih inovatif.